An Ultrasound Automated Method for Non-Invasive Assessment of Carotid Artery Pulse Wave Velocity. (August 2018) - Zardi, Enrico Maria; Di Geso, Luca; Afeltra, Antonella; Zardi, Domenico Maria; Giorgi, Chiara; Salaffi, Fausto; Carotti, Marina; Gutierrez, Marwin; Filippucci, Emilio; Grassi, Walter
To validate the clinical applicability and feasibility of an automated ultrasound (US) method in measuring the arterial stiffness of patients with chronic inflammatory rheumatic diseases, comparing automated measurements performed by a rheumatologist without experience in vascular sonography with those obtained by a sonographer experienced in vascular US, using a standardized manual method. Twenty subjects affected by different chronic inflammatory rheumatic disorders were consecutively recruited. For each patient, the arterial stiffness of both common carotids was manually calculated. Subsequently, the measure of the pulse wave velocity (PWV) was obtained using an US device called Radio Frequency - Quality Arterial Stiffness (RF-QAS), provided by the same US system (ie, My Lab 70 XVG, Esaote SpA, Genoa, Italy) equipped with a 4–13 MHz linear probe. The reliability comparison between the two US methods was calculated using the intraclass correlation coefficient (ICC). ICC between the values obtained with the two methods for calculating the arterial stiffness resulted 0.789. A significant positive correlation between the two methods was also established with Pearson's (r=0.62, p<0.0001) and Spearman's analysis (r=0.66, p=0.001). A significant performance comparison was seen using Bland-Altman plot. The acquisition of the arterial stiffness parameter with the automated method required about 2 min for each patient. Clinical applicability of this US automated method to assess PWV at common carotid level by a rheumatologist is reliable and feasible in comparison with a conventional manual method.